Residential proximity to an industrial incinerator and risk of soft-tissue sarcoma, 1999-2014 - Benedetti, Marta; Fazzo, Lucia; Guarda, Linda; Gatti, Luciana; Comba, Pietro; Ricci, Paolo (Epidemiologia e prevenzione, 2020)
exposure to dioxins has been associated with an increased risk of soft-tissue sarcoma (STS). In a study relating to 1989-1998, a significant excess of STS was found in the population living within a 2-kilometre radius of an industrial incinerator located inside a Mantua industrial site. In the years 1974-1991, the incinerator burned hazardous chlorine-containing waste that resulted in the emission of dioxins. After 1991, it was exclusively fed with organic synthetic products not containing chlorine. the aim of this case-control study was to estimate the STS risk, for 1999-2014, in the population living in four Mantua districts located in the proximity of the industrial incinerator, compared to subjects resident in the remaining parts of Mantua province, regarded as non-exposed. the cases analysed were subjects with a first-incident diagnosis of STS between 1999 and 2014 resident at diagnosis in Mantua Province. Cases were selected using the 2013 criteria from the WHO classification. Cases of Kaposi sarcoma, PEComas and STS occurring in a previously irradiated field were excluded. For each case of soft-tissue sarcoma, four controls were randomly selected from all individuals resident in Mantua Province included in the Regional Health Service database in the years of incidence of each case (calendar year), and individually matched for gender and year of birth. Residential and occupational history (for employment in an oil refinery, and petrochemical and chemical plants) was reconstructed for all study subjects (cases and controls) since 1961. Subjects were considered exposed if they had lived in the four Mantua districts most affected by the incinerator emissions, on the basis of an atmospheric dispersion model and a dioxins biomonitoring survey. Four analyses were performed according to variously defined residential time windows. Odds ratios and corresponding 95% confidence intervals (95%CI) were calculated using conditional regression models adjusted for occupational history. 391 cases (203 males and 188 females) and 1,564 controls were included. The number of exposed cases and controls in the four analyses were 8 and 55, 8 and 60, 15 and 68, and 15 and 73, respectively. An increased STS risk was not observed in any of the analyses. in this study, no increased risk of STS was observed in subjects who had lived, in the study's time window, in the Mantua districts most affected by the incinerator emissions. The most likely interpretation of the present finding is a real STS risk reduction for subjects resident in the most recent decades in the Mantua districts most affected by the incinerator emissions, due to the cessation of burning chlorine-containing waste in the incinerator, development of some remediation plans, and implementation of new industrial procedures.